Analysis of heterologous protein production in defined recombinant Aspergillus awamori strains. - Gouka, R J (1996)
A study was carried out to obtain more insight into the parameters that determine the secretion of heterologous proteins from filamentous fungi. A strategy was chosen in which the mRNA levels and protein levels of a number of heterologous genes of different origins were compared. All genes were under control of the Aspergillus awamori 1,4-beta-endoxylanase A (exlA) expression signals and were integrated in a single copy at the A. awamori pyrG locus. A Northern (RNA) analysis showed that large differences occurred in the steady-state mRNA levels obtained with the various genes; those levels varied from high values for genes of fungal origin (A. awamori 1,4-beta-endoxylanase A, Aspergillus niger glucoamylase, and Thermomyces lanuginosa lipase) to low values for genes of nonfungal origin (human interleukin 6 and Cyamopsis tetragonoloba [guar] alpha-galactosidase). With the C. tetragonoloba alpha-galactosidase wild-type gene full-length mRNA was even undetectable. Surprisingly, small amounts of full-length mRNA could be detected when a C. tetragonoloba alpha-galactosidase gene with an optimized Saccharomyces cerevisiae codon preference was expressed. In all cases except human interleukin 6, the protein levels corresponded to the amounts expected on basis of the mRNA levels. For human interleukin 6, very low protein levels were observed, whereas relatively high steady-state mRNA levels were obtained. Our data suggest that intracellular protein degradation is the most likely explanation for the low levels of secreted human interleukin 6.